Pemahaman dan Pengamalan Surat Al Jumuah Ayat 9-10 (Studi Kasus Pada Pedagang di Lingkungan Masjid Ampel Surabaya) - Abdullah, Fahmi; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study analyzes understanding of merchants of surah Al Jumuah verses 9-10. Understanding that examined about when sounding the call Athan all activities (sale and purchase) must be abandoned immediately and promptly carry out the Friday prayers, and back doing activities (sale and purchase) when finished doing the prayer Friday. This research used the qualitative approach with case studies. Data collection was done with interviews and observations directly to the object/subject of research. The results of this research show that the level of understanding of respective merchants of surah Al Jumuah verses 9-10 good and different so that the impact on the implementating. In addition, they believe in running the prayer Friday positively impact of sustenance, though not directly. A positive impact not only sustenance, but by hearing sermons Friday prayers will add to the sense of faithfulness to God Almighty.